Pregnant Women in Trials of Covid‐19: A Critical Time to Consider Ethical Frameworks of Inclusion in Clinical Trials - Farrell, Ruth; Michie, Marsha; Pope, Rachel (Ethics & human research, 2020)
ABSTRACT Ethical issues abound during this unprecedented international public health crisis of Covid‐19. While the trade‐off between societal and individual interests that occurs at the intersection of public health ethics and clinical ethics affects all populations, this calculus has particular relevance for pregnant women and the question of when they will have access to new Covid‐19 therapies and vaccines. Pregnant women are a “scientifically complex” population whose inclusion in clinical research must be done with consideration of the unique state of pregnancy. Yet research on the impact of Covid‐19 on pregnant women is lagging. In a rush to prevent and treat SARS‐CoV‐2 infection, it is crucial that the interests of pregnant women be prioritized to enable them to make autonomous, informed decisions about participating in clinical trials. The global pandemic calls for a revisiting of frameworks for the inclusion of pregnant women in research, as these women have an important stake in the prevention and treatment of Covid‐19.